Cross-transfer effect of upper body exercises to leg power - Dalipe, Regina Mae P.
Cross-education is a type of training that transfers strength to other parts of the body that are untrained. The main reason behind this phenomenon is due to the adaptations in the neural system through resistance training. For physically active individuals, there is always the risk of getting injured. Leg power is essential especially to sports that require explosive movements such as jumping, sprinting, and change of direction. To prevent loss of strength and muscle atrophy in the limbs caused by injury, cross education training can improve, maintain, or regain strength and power. For this study, it investigated the effects of upper body training only on leg power and it showed that it is possible to gain power. A paired t-test was used to compare the pre and post test scores of the participants at 0.05 level of significance. Both vertical and horizontal test scores showed a significant difference. Thus, rejecting all null hypotheses. The participants in this study were 10 young female adults aged 20-24 years old who reside in Quezon City. Their training background was at least 6 months of no involvement in regular physical activities. Training parameters that are tested are the distance of a broad jump and vertical jump height through the use of a measuring tape. A total of 12 sessions was done, excluding the testing days, with a frequency of 3 times a week in a span of 4 weeks. Progressive overload in exercises were applied and a day interval was allotted for the participants to recover well since they are sedentary individuals.